Popularity and parity assessment for more inclusive and balanced aquaculture development - Junning Cai; PingSun Leung (Scientific Reports)
Abstract Aquaculture, a rapidly expanding food production system, holds promise for improving global food security and resilience. However, imbalanced growth has led to a highly uneven distribution of aquaculture production among countries, a concern that has not been comprehensively examined. This paper fills this knowledge gap by developing an innovative indicator system to assess this issue based on aquaculture development in ~ 200 countries over five decades. The system utilizes the “effective number of countries” (ENC) as a basic measure of production distribution and extends it into two novel indicators, popularity and parity, to gauge inclusiveness and balance. The assessment from 1970 to 2020 reveals that aquaculture has become a global enterprise, operating in nearly 90% of countries. Nevertheless, there is still substantial potential for growth in aquaculture popularity across most of 43 species groups examined here. Regarding concerns over persistently imbalanced aquaculture growth, our assessment reveals that aquaculture parity increased during 1970–2020 in the majority of 85 country groups examined here, including 18 of 27 regions and subregions. Global parity is also on the rise in the new millennium (2000–2020). However, the global aquaculture parity remains considerably lower than those of capture fisheries and terrestrial meat production. This suggests that imbalanced global aquaculture development cannot be solely attributed to countries’ comparative advantages. This extraordinary imbalance could compromise global food security and food system resilience, but it also signifies untapped growth potential. Mainstreaming aquaculture popularity and parity as policy indicators can foster more inclusive and balanced development and unlock this potential. The proposed indicator system can be applied across diverse sectors and scales, contributing to a broader and refined understanding of the dynamics within the global food system.